Kadar Protein, pH dan Jumlah Bakteri Asam Laktat Yoghurt Susu Sapi dengan Variasi Penambahan Sari Daun Kelor dan Lama Fermentasi yang Berbeda - Rahmawati, Endang, Dr. Nanik Suhartatik, S.TP., M.P (2015)
Yoghurt was a popular fermented drink in the world and benefit for health of the body was usually made from cow's milk. Yoghurt could be innovated by adding a substance that could improved the nutritional quality and distinctive taste, one of them with extract of moringa leaves. Moringa leaves contain protein, carbohydrates, calcium, vitamins, tannins, flavonoids, steroids and saponins. The purpose of this study to investigate protein content, pH, and total of lactic acid bacteria inside the yoghurt. The research method with a completely randomized design with two factors: factor 1,extract Moringa leaves concentration (K): 0%, 5%, 10% and factor 2, fermentation period (hours) (F): 8, 10, 12. The results showed that the highest levels of protein in the treatment K1F2 (extract of Moringa leaves 5% : fermentation period 10 hours) was0.870%, while the lowest protein content in treatment K0F1 (extract of Moringa leaves0%: fermentationperiod 8 hours) was 0.179%. Interaction between various addition extract of Moringa leaves and fermentation period significantly affected the pH yoghurt. The highest total of lactic acid bacteria in the treatment K1F1 and K1F2 with the same number that was 2,50 x107 CFU/ml and the lowest in treatment K0F1 1,0x107 CFU/ml.